(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Thepresent study introduces a number of observations on the applications ofinformation technology (IT) in the field of human resource management (HRM) ingeneral. The human resource management necessary to meet the new conditions andfind So that the capacity utilization of information technology can provide,Human resources will improve performance. In this study is a brief history ofboth information technology and human resource management provides And theimpact and consequences of information technology on human resource managementfunctions explain. HRM (human resourcemanagement) is especially important in a knowledge-based economy, where ideasand expertise are greatly valued, and a creative and innovative workforce isnecessary to meet the challenges of this new economy. Efficient and effectivemanagement of human capital is increasingly an imperative and complex process.As a result, there has been a considerable increase in the number oforganizations gathering, storing, and analyzing information regarding their HRsthrough the use of software which is HRIS (human resource information system).The growing importance of HRIS is due to the recognition of HR practitionersthat IT (information technology) and IS (information system) should be a partof HR functions mainly to develop and use better HRM programmes.